Er barnet blevet givet tilbage? - Buhl-Nielsen, Bernadette; Henanger, Camilla (Psyke & Logos, 2016)
This article looks at the problem of deliberate self-harm in subjects with personality disorder from the perspective of Winnicott’s theories regarding the development of a true self, in combination with perspectives from social psychology and attachment theory. The mirror interview, in which subjects are interviewed whilst looking at themselves in a full-length mirror, was used to assess the degree of body esteem and alienation expressed by subjects with and without acts of deliberate self-harm. Qualitative analysis was used to analyze six interviews in depth with the aim of getting a clearer insight into potential mechanisms that could lead to acts of deliberate self-harm. It was found that subjects with personality disorder and deliberate self-harm had a tendency to be ashamed of and even despise their bodies. They also displayed a painful sense of alienation towards their mirror image and had problems in reconciling a first person perspective on the self with a third person perspective. A project is underway to test these hypotheses quantitatively and if found to be statistically significant, this type of self-disturbance could help the clinical understanding and treatment of deliberate self-harm.